Challenges faced in the application of information and communication technology in the teaching and learning of business studies at Advanced Level in Shurugwi district. - Ndluvu, Graciano R. (Midlands State University, 2017)
The purpose of the research was to investigate the challenges faced in the application of ICT in the teaching and learning of Business studies at Advanced Level in Shurugwi District. To carry out the study, the researcher used the descriptive survey design. Shurugwi consisted of five high schools. The researcher used a sample of three high schools. The sample was made up of thirty students, six teachers, three school heads. The researcher used the stratified and random sampling techniques in sampling the students. She used the hat system to select the students who participated in the study. Questionnaires, interviews and observations were used for data collection. The findings from the sample were presented in the form of tables and graphs and were discussed and linked with the related literature. Findings from the study revealed that the main challenges that were faced in ICT application in teaching and learning processes were lack of access to resources, lack of technical assistance, interrupted power cuts and high costs of computer hardware and software. The research recommends teacher training and development, schools to source more tools to enhance the application of ICT in education, schools improve infrastructure and schools employ emergency technical personnel.